How work environment lead to performance? - Wahyu Kurniawan; Suhartini Suhartini; Andriyastuti Suratman (Inovbiz: Jurnal Inovasi Bisnis, 2023)
This study seeks to confine the effect of the work environment relationship on improving employee performance and the impact of performance evaluation on employee performance. The variables of this study consist of the independent variables, namely work environment and performance evaluation, and the dependent variable, namely employee performance. This study uses a method in the form of a quantitative approach, with the data collection tool used as an online questionnaireâ€”a sample of 101 respondents using a non-probability sampling method. Data analysis in this study used Partial Least Squares (PLS) with SmartPLS v.3.3 software. The study's outcomes reveal that the work environment variable positively affects employee performance. At the same time, performance evaluation does not involve improving employee performance.Â